Cariotipo del pejelagarto tropical Atractosteus tropicus (Lepisosteiformes: Lepisosteidae) y variación cromosómica en sus larvas y adultos - Arias-Rodríguez, Lenin (2009)
The karyotype of the tropical gar Atractosteus tropicus is described from conventional Giemsa-staining of 295 mitotic chromosome slides from 120 larvae and 15 adults (five females and ten males) from Tabasco, southern of Mexico. The diploid number 2n = 56 chromosomes was calculated (73 spreads from 206 larval and 208 adult metaphases). Variation on chromosome number was from 46 (4.4%) to 64 (3.9%) chromosome elements on larval samples, whereas 58 (11.7 %) chromosomes were the second most abundant after the diploid number of 2n = 56 (35%). Such variation was related with the presence of mobile microchromosomes. The karyotype was determined from six clear chromosome spreads photographed from three females and three males. The averaged karyotype was integrated by eight pairs of metacentric (m) chromosomes, four submetacentric (sm) pairs, eight telocentric (t) pairs and eight pairs of telocentric micro-chromosomes (*t). The fundamental number was FN = 80 chromosome arms. We saw no sexual differences on chromosome structure.